Ikan teri Engraulis encrasicolus berpotensi sebagai pangan fungsional - Wa Ode Salma; Ruwiah Ruwiah; Febriana Muchtar; Nabilah Hanum Mudjahidah; Karwika Dwi Saputri Nurdin; Muhammad Rahmat Bastaman (AcTion: Aceh Nutrition Journal, 2021)
Anchovy Engraulis encrasicolus is a good prospect to be developed in the future, maybe it can be used for hyperlipidemia diet.  This study, therefore, aims to measure and assess the content of EPA (eikosapentaenoat acid)  and DHA (docosahexaenoic acid).from Anchovy Engraulis encrasicolus  oil extract. The samples were obtained from the city of Kendari in Southeast Sulawesi, Indonesia. It was processed and manufactured at the Halu Oleo University in Pharmacy Laboratory. Furthermore, the extraction process utilized the Soxhlet method, while measuring and analyzing the content of EPA and DHA using UV/Vis Spectropometric. It was found that 25 mg of Anchovy Engraulis encrasicolus oil produced DHA levels of 145,5 mg/g (14,5%) and EPA levels of 97,15 mg/g (7,71%). Anchovy Engraulis encrasicolus is a potential for functional food used to provide protection against diseases associated with metabolic disorders and diet hyperlipidemia.